Relationship of Knowledge Level of Teenagers About The Use of Tight Jeans with Fluor Albus Whitish Incident in High School Pembangunan Bukittinggi Year 2017 - Claurentica, Debrina; Putri, Rima Berlian (LPPM Universitas Prima Nusantara Bukittinggi, 2018)
Reproductive health is a state of complete physical, mental and social well-being, which is not solely free of disease or disability, in all matters relating to the reproductive system, as well as its functions and processes. The fact is still found many teenage girls who wear tight jeans and do not know that the use of tight jeans can affect the reproductive health of one occurrence of whiteness (Fluor Albus). The purpose of this study is to determine the relationship of the knowledge level of young women about the use of tight jeans with Fluor Albus whiteness in High School Pembangunan Bukittinggi Year 2017. This research method using a descriptive correlation method with Cross-Sectional approach design, then data is processed by using the Chi-Square test. The population in this study were 118 respondents. The sample in this research is 55 respondents with Probability Sampling technique on 15 to 16 August 2017 in Bukittinggi Pembangunan High School. Univariate results obtained from 55 respondents there are more than half of 31 (56.4%) of respondents have high knowledge, more than half 29 (52,7%) of respondents did not occur whiteness. The result of statistical test obtained p-value = 0,000 (p <Î±) which means there is a relationship of knowledge with the incidence of whiteness (fluor albus) in High School Pembangunan Bukittinggi Year 2017. The conclusion of the relationship of knowledge with the incidence of leucorrhoea (fluor albus) in High School Pembangunan Bukittinggi Year 2017. It is expected that teenagers to pay more attention to reproductive health on female students. So as to prevent and detect early existence of reproduction organ problem.